2000
DOI: 10.2466/pms.2000.90.2.399
|View full text |Cite
|
Sign up to set email alerts
|

Coaches' Expectations and Beliefs regarding Benefits of Youth Sport Participation

Abstract: Although many have investigated why children participate in sport, little is known about what adults expect children to gain from participation. The present purpose was to examine coaches' expectations of what children should gain from participation in sport and the extent to which coaches believe that these expectations are actually fulfilled. Participants included 109 youth sport coaches who completed a survey packet consisting of a demographic information questionnaire and the Ohio Sport Satisfaction Index.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 2 publications
1
9
0
Order By: Relevance
“…A commitment by coaches to learning and learners is seen as a fundamental aspect of good coaching (Penney, 2006). The coaches drive the ethos and this fits in with the findings of Lesyk and Kornspan (2000) that they want the players to have the key ingredients of fun, life skills, enjoyment, and teamwork. The fact that the children are enjoying the experience means they are far more likely to carry on playing sport into adulthood (Kirk, 2006).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…A commitment by coaches to learning and learners is seen as a fundamental aspect of good coaching (Penney, 2006). The coaches drive the ethos and this fits in with the findings of Lesyk and Kornspan (2000) that they want the players to have the key ingredients of fun, life skills, enjoyment, and teamwork. The fact that the children are enjoying the experience means they are far more likely to carry on playing sport into adulthood (Kirk, 2006).…”
Section: Discussionsupporting
confidence: 56%
“…The traditional role of the coach is stereotyped as telling the participants what to do and the role of the participants is to listen, absorb, and comply (Lesyk and Kornspan, 2000;Romar et al, 2016) found that coaches want their participants to have fun, learn life skills, be part of a team, develop confidence, and have the excitement of competition. Providing the young participants with an ownership of their own participation will play a significant role in achieving some of these outcomes (Romar et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As with the studies that focused on positive self-concept, there is both qualitative (Camiré et al, 2011 , 2012 ) and quantitative (Lesyk & Kornspan, 2000 ) evidence demonstrating how coaches see themselves as responsible for the development of life skills in athletes under their guidance. Moreover, qualitative studies showed how youth athletes themselves believe that sport can teach them important life skills that can be applied to non-sport-related pursuits (e.g., Camiré et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…One example from this research was the negative impact of a win-at-all-costs coaching philosophy (e.g., Buford-May, 2001 ). While many papers included in the review noted the important role that coaches play in shaping the overall sport experience (e.g., Camiré et al, 2011 ; Gould et al, 2012 ; Lesyk & Kornspan, 2000 ; MacDonald et al, 2010 ; Rutten et al, 2007 ), less research examined the characteristics of coaches that shape youths’ experience in sport.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the classroom, researchers have regularly associated sport participation with enhancing the physical, psychological, and social well-being of youth (Bailey, 2006;Côté & Fraser-Thomas, 2007;Fraser-Thomas, Côté, & Deakin, 2005;Lesyk & Kornspan, 2000;Vanresusel et al, 1997;Weirsma, 2000). Here, specific to the Canadian context, True Sport, an organization dedicated to using sport as a vehicle for positivity in local communities, produced a comprehensive report on the value of sport to Canadian society.…”
Section: Introductionmentioning
confidence: 99%